Biomechanical study of midpalatine suture and miniscrews affected by maturation of midpalatine suture, monocortical and bicortical miniscrew placement in bone-borne rapid palatal expander: a finite element study - Sermboonsang, Chayapa; Chantarapanich, Nattapon; Inglam, Samroeng; Insee, Kanlaya (Science, Engineering and Health Studies, 2020)
This study aimed to investigate the biomechanical performance of different miniscrews placement techniques in different stages of midpalatine suture maturation using finite element analysis. Four models of partial nasomaxillary structure with bone-borne rapid palatal expander were constructed with monocortical and bicortical placement types with partly ossified midpalatine suture and completed ossified midpalatine suture. From the finding, both monocortical and bicortical techniques is able to separate partly ossified suture. The separation of completed ossified midpalatine was even more difficult than partly ossified suture because the separation was not clearly observed and higher stress exhibited on expander. However, the bicortical placement technique was observed to be more parallel pattern of suture expansion. In all Finite Element (FE) cases, von Mises stress exhibited on neck and upper intraosseous part of miniscrew in monocortical model. In midpalatine suture, the bicortical model can produce high stress in superior and inferior region of midpalatine suture, whereas monocortical can diffuse only inferior of suture. The completed ossified midpalatine suture shows low stress level along the suture and has insignificant displacement. The elastic strain pattern at peri-implant site in monocortical model was high at medial tip and lateral at cortical margin. For bicortical model, the elastic strain concentrated at upper intraosseous. The bicortical placement technique has more advantages in promote parallel maxillary bone expansion, decrease deformation risk and increase stability of appliance.